2013
DOI: 10.1142/s0218625x13500558
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SILICON DOPING IN CVD DIAMOND FILMS FROM MICROCRYSTALLINE TO NANOCRYSTALLINE ON WC-Co SUBSTRATES

Abstract: Si-doped diamond¯lms with various Si concentrations are deposited on WC-Co substrates using HFCVD method, with the mixture of acetone, tetraethoxysilane (TEOS) and hydrogen as the reactant source. A variety of characterizations, including FE-SEM, AFM, Raman, XRD, surface pro¯lometer and Rockwell indentation, are conducted to systematically investigate the in°uence of Si incorporation on diamond¯lms. As the Si/C ratio from 0% to 5%, the grain size of as-deposited lms decreases from 4 m to about 50 nm, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The deposition of diamond coatings are completed in the hot filament CVD apparatus, in which the tantalum wires are used as hot filaments. The acetone is introduced as a carbon source using the bubbling method as descripted in [13]. During the deposition, the temperatures of hot filaments and the substrate surface are 2200 ± 100 • C and 900 ± 100 • C. And the negative bias voltage has been added with 40 V through the electrode poles.…”
Section: Deposition and Characterizationmentioning
confidence: 99%
“…The deposition of diamond coatings are completed in the hot filament CVD apparatus, in which the tantalum wires are used as hot filaments. The acetone is introduced as a carbon source using the bubbling method as descripted in [13]. During the deposition, the temperatures of hot filaments and the substrate surface are 2200 ± 100 • C and 900 ± 100 • C. And the negative bias voltage has been added with 40 V through the electrode poles.…”
Section: Deposition and Characterizationmentioning
confidence: 99%
“…The added impurities can affect the gas phase reactions, the surface mobility of the carbon species, fluid dynamics and chemical reaction kinetics . What's more, we have reported that boron and silicon doping can affect the tribological properties and cutting performance of diamond films . Thus, the investigation of the doped diamond films on WC–Co substrate has practical significance.…”
Section: Introductionmentioning
confidence: 99%